Magnitude of Psychological Distress Among Medical and Non-Medical Students During the Late Phase of the COVID-19 Pandemic in West Bengal: A Cross-Sectional Study - Udisa Das; Arunima Ganguly; Dibakar Haldar; Asish Mukhopadhyay (International Journal of Medical Students)
Background: COVID-19 pandemic led to drastic changes worldwide significantly affecting mental health of students. This study aimed to assess psychological distress due to COVID-19 in students during the late phase of pandemic and to establish correlation of academic course, socio-demographics and knowledge-attitude-practices (KAP) with depression and anxiety.